Fungal saprobes and pathogens occurring on tissues of Dracaena lourieri and Pandanus spp. in Thailand - Thongkantha S. (2014)
Studies of fungi on Dracaena and Pandanus were initiated in Thailand in order to investigate the biodiversity of fungi from wild and cultivated Dracaena lourieri, Pandanus amaryllifolius P. penetrans and P. odoratissimus. One-hundred and twenty-seven saprobes were found on decaying tissues, particularly on leaves, and comprised 40 ascomycetes, 1 basidiomycete and 86 anamorphic taxa. Eight ascomycetes and 3 anamorphic taxa were new to science. Distinct fungal communities were found on samples of Dracaena and Pandanus species. In terms of the numbers of taxa recovered, fungi were more diverse on wild species than on the cultivated species. Fifty-five fungal taxa were identified from leaf baits of Pandanus penetrans hung on host plants in Doi Suthep Pui National Park during the decomposition process. Distinct fungal communities were observed in sequence on the leaf baits, with different species being dominant at each succession stage. The highest fungal diversity occurred between months 7 and 12 (mature stage). At month 18, the leaf baits were found to be skeletonised, so the fungal communities had decreased in number. Only half of the taxa identified from P. penetrans occurred on both baits and natural leaves. Twenty-three fungi were identified from samples showing symptoms of anthracnose on leaves, leaf blast or leaf spots. Factors affecting the colonization of fungi on Draceana and Pandanus are discussed.